IMPLEMENTANSI BALANCED SCORECARD SEBAGAI ALAT UKUR PENILAIAN KINERJA UMKM PUTIH TELUR JOGJA (SINAR SENTOSA) - Almas, Salsabila; Puspita, Della; Lastiati, Anies (KEUNIS, 2023)
This study aims to evaluate the effectiveness of the company's strategy with the Balanced Scorecard as a performance measurement tool. The research method used is descriptive qualitative based on primary data through interviews and observations of MSME actors and literature that supports the research. The results of the research based on interviews show that UMKM Putih Telur Jogja (Sinar Sentosa) in implementing the Balance Scorecard which consists of a Financial Perspective, Customer Perspective, Internal Process Perspective, and Learning and Growth Perspective has been carried out well. However, there are several perspectives that need to be improved by looking at the opportunities that exist, namely the Customer Perspective and Learning and Growth Perspective.